The Institutional Grammar: Evolving Directions in Current Research - Saba Siddiki; Ute Brady; Christopher K. Frantz (International Review of Public Policy)
This article introduces the special issue of the International Review of Public Policy devoted to “Exploring Institutional Dynamics with the Institutional Grammar”. In doing so, it: (i) provides a brief introduction to the Institutional Grammar as an increasingly prominent tool for the study of institutions that govern social systems, such as public policies and social conventions; (ii) describes evolving trends in Institutional Grammar research reflected in and beyond the papers included in the issue; and (iii) discusses analytical trade-offs associated with these trends, with specific reference to special issue papers. This introduction to the special issue thus contextualizes the research presented in the issue, while also offering insights and guidance regarding the ongoing use and development of the Institutional Grammar.